Integration of SDGs, Global Citizenship, and Pancasila Values in Civic Education Learning in Elementary Schools: Education for Sustainable Development (ESD) Framework to Prepare for a Sustainable Generation - Mukhlis, Septian; Setiawan, Bramianto; Fauzi, Ahmad; Fikriyah, Mely Adinda; Sulistiawati, Anastasya; Iasha, Vina (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the integration of the Sustainable Development Goals (SDGs), Global Citizenship Education (GCED), and Pancasila values in Civic Education (PKn) learning at the elementary school level through the framework of Education for Sustainable Development (ESD). A qualitative approach was employed involving elementary school teachers and students as research participants. Data were collected through interviews, observations, and document analysis and were analyzed thematically. The findings reveal that SDGs serve as a learning context by introducing real-world issues such as environmental sustainability, health, education, and social justice. GCED contributes to the development of global citizenship competencies, including tolerance, respect for diversity, collaboration, social responsibility, and peaceful conflict resolution. Meanwhile, Pancasila values function as a normative foundation that guides students in understanding and applying the principles of sustainable development and global citizenship in accordance with the Indonesian national character. The integration of these three components creates a contextual and relevant Civic Education learning framework that fosters students who are morally grounded, sustainability-conscious, and prepared to participate actively in a global society.